Different creep compound feed formulations for new born piglets: influence on growth performance and health parameters - Badaras, Sarunas; Ruzauskas, Modestas; Gruzauskas, Romas; Zokaityte, Egle; Starkute, Vytaute; Klupsaite, Dovile; Mockus, Ernestas; Klementaviciute, Jolita; Vadopalas, Laurynas; Zokaityte, Gintare; Dauksiene, Agila; Bartkevics, Vadims; et al. (Frontiers in Veterinary Science, 2022)
The aim of this study was to compare the influence of different compositions of creep compound feed (CCF) (C-I – control group; TG-II – a CCF containing wheat bran extruded and fermented with L. paracasei; TG-III – a creep compound feed containing sugar beet pulp) on the piglets' growth performance, blood parameters, fecal microbial profile and physicochemical characteristics. Moreover, the fecal volatile compound (VC) profile was analyzed as a possible chemical marker related to changes in the fecal microbial profile and physicochemical characteristics. A 21-day experiment was conducted using 1-day-old 300 Large White/Norwegian Landrace piglets. The highest body weight (at the 21st day) was found in piglets of the TG-III group, and both treated groups showed lower feed conversion ratios. At the end of the experiment, significantly higher lactobacillus counts in the feces of both treated groups were found, and a correlation between fecal textural hardness and the lactobacillus count was established (r = 0.475). Significant correlations of piglets' individual fecal VC with microbiological parameters and fecal pH were established [lactobacilli with 3-n-nonadecanol-1; enterobacteria with butyric acid <2-methyl->; pentanoic acid, 4-methyl-; eicosene(E)-, etc.]. It can be concluded that local material could be successfully incorporated into CCF preparation without impairing animal metabolism.